2020
DOI: 10.1111/jgs.16791
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Prevention and Screening for Older Adults: Part 1. Lung, Colorectal, Bladder, and Kidney Cancer

Abstract: The incidence of most cancers increases with age. Cancer is the second most common cause of death in older adults after cardiovascular disease. Many common cancers in older adults can be prevented from occurring or can be identified at an early stage and treated effectively. The prevention and identification of cancer in its early stages, in an attempt to reduce discomfort and disability associated with advanced cancer and cancer treatment, is also a priority. Overscreening for cancer in older adults can lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Frailty-based biological age = −0.803 × FDS 2 + 12.34 × FDS + 59. 8 We observed a "moderate" association between the chronological ages and FDS (R 2 = 0.332, Figure 2A).…”
Section: Control Individuals and Estimation Of Frailty-based Biologic...mentioning
confidence: 80%
See 2 more Smart Citations
“…Frailty-based biological age = −0.803 × FDS 2 + 12.34 × FDS + 59. 8 We observed a "moderate" association between the chronological ages and FDS (R 2 = 0.332, Figure 2A).…”
Section: Control Individuals and Estimation Of Frailty-based Biologic...mentioning
confidence: 80%
“… Study population and design. We developed the FDS in Study 1 (training set) and validated in the utility of FDS in Study 2 (validation set), which were reported in the previous study (*, refs [ 7 , 8 ]). The definition of the expected life age (years) = [ chronological age + life expectancy ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the incidence rate of colorectal can-cer has shown a gradual increasing trend with the improvement of the living standard [13]. Surgery is the cornerstone of various treatments for colorectal cancer, but the surgical trauma is large, and patients suffer great physical and mental pain during perioperative period [14][15][16]. Although the current implementation of neoadjuvant therapy has reduced the recurrence rate of local lesions and increased the possibility of anus preservation, a considerable number of patients still have local recurrence due to the particularity of the physiological and anatomical location of the colorectal part and the lymphatic drainage pathway [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the basis of pursuing frailty assessment in different settings of onconephrology could be justified from two major dimensions. Firstly, the prevalence of kidney cancer, concurrent cancer with CKD, AKI with cancer, and treatment-associated nephrotoxicities in cancer patients are significantly greater amongst older patients [ 67 , 68 , 69 ]. Older patients with cancer tend to have greater levels of frailty in comparison to individuals without cancer [ 17 ].…”
Section: Clinical Significance Of Frailty Assessment In Onconephrologymentioning
confidence: 99%